The urgency of Public Service Malls in realizing good governance in Indonesia - Widnyani, Ida Ayu Putu Sri; Anantanathorn, Anurat; Rahayu, Ni Made Pitri (Goodwood Publishing, 2024)
Purpose: This study aims to analyze the urgency of establishing and developing Public Service Malls (MPP) as a strategic instrument for realizing the principles of good governance in Indonesia. Research methodology: Using a literature review approach, this study examines the relationship between the existence of MPPs and the main elements of good governance, such as transparency, accountability, efficiency, and responsiveness. Results: The findings reveal that PSMs significantly contribute to the transformation of public services by integrating diverse government and private services into one-stop centers. This integration reduces bureaucratic complexity, accelerates service delivery, enhances public trust, and promotes institutional accountability in the public sector. Furthermore, this study highlights the importance of adopting the pentahelix collaboration model, which engages the government, academia, business, civil society, and the media, to optimize the role of PSMs in governance reform. Conclusions: PSMs represent a strategic solution to persistent governance challenges in Indonesia by fostering innovation, improving accessibility, and ensuring citizen-oriented public services. They are essential for achieving bureaucratic reform objectives and advancing sustainable governance practices. Limitations: This research relies exclusively on secondary data sources, limiting its ability to capture the first-hand experiences of service users and practitioners. Regional variations in PSM implementation have not been fully addressed due to the uneven availability of empirical studies. Contribution: This study contributes to the academic discourse on governance innovation by conceptualizing public service motivation (PSMs) as a practical embodiment of good governance principles. It also offers policy recommendations for strengthening digitalization, expanding public participation, and institutionalizing cross-sector collaboration through the pentahelix model, thereby providing a roadmap for enhancing public service governance in Indonesia.